2021
DOI: 10.1159/000513813
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Cognitive and Visual Function in a Nationally Representative Study of Older Adults in India

Abstract: Introduction: Due to population aging, India is poised to experience a large increase in the burden of both dementia and vision impairment (VI). Prior studies from other settings suggest that VI may be a modifiable risk factor for cognitive decline and dementia. However, to date, no studies have examined the association of impaired visual acuity and cognition in India. Methods: A total of 3,784 participants in wave 1 of the population-based Diagnostic Assessment of Dementia for the Longitudinal Aging Study in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…On the contrary, the prevalence of diabetes among older individuals was negatively associated with VI in our study which is at variance with previous studies showing a positive association of diabetes mellitus with VI and blindness [ 49 , 50 ]. This unexpected finding may be explained by the fact that older adults who self-reported diagnosis of diabetes might have received routine medical care and eye exams and utilized vision enhancing interventions like eyeglasses and cataract surgery as well as were more likely to have proper compliance with medicine [ 51 ]. However, since diabetes is known to be an important cause of VI and blindness in India and across the globe [ 52 ], the current finding requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the prevalence of diabetes among older individuals was negatively associated with VI in our study which is at variance with previous studies showing a positive association of diabetes mellitus with VI and blindness [ 49 , 50 ]. This unexpected finding may be explained by the fact that older adults who self-reported diagnosis of diabetes might have received routine medical care and eye exams and utilized vision enhancing interventions like eyeglasses and cataract surgery as well as were more likely to have proper compliance with medicine [ 51 ]. However, since diabetes is known to be an important cause of VI and blindness in India and across the globe [ 52 ], the current finding requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that 80% of visual impairment can be corrected [7] . Refractive error is the most common visual impairment and presents a growing incidence; moreover, it is a risk factor for Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 98%
“…MCI prevalence in low and middle-income countries ranged from 0.3% to 63.3%, while the prevalence in Malaysia ranged from 15.8% to 21.1% [11] . Reduced vision is associated with cognitive decline [12][13][14][15][16][17] . The sensory deprivation hypothesis states that a decline in visual perception over time leads to gradual neural degradation and consequently reduced cognition [18] .…”
Section: Introductionmentioning
confidence: 99%